Republic of Croatia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Croatia. (IMF Staff Country Reports; Country Report ;, 2021)
As other emerging economies reliant on tourism (about 25 percent total contribution of tourism-related industries in GDP and employment), Croatia has been hit hard by the pandemic and two devastating earthquakes, leading the economy to contract by 8.0 percent in 2020. Vaccinations have been rolled out to about 38 percent of the population (end-June 2021). Staff projects growth to bounce back to 5.4 percent in 2021, driven by a rebound in the services sector and investment, aided by fiscal and monetary policies, and bolstered by large EU grants over the medium-term.